Testing Normality and Bandwith Estimation Using Kernel Method For Small Sample Size - Netti Herawati; Khoirin Nisa (Jurnal ILMU DASAR, 2009)
This article aimed to study kernel method for testing normality and to determine the density function based on curve fitting technique (density plot) for small sample sizes. To obtain optimal bandwith we used Kullback-Leibler cross validation method. We compared the result using goodness of fit test by Kolmogorof Smirnov test statistics. The result showed that kernel method gave the same performance as Kolmogorof Smirnov for testing normality but easier and more convinient than Kolmogorof Smirnov does.